Aumentar la gramática discursiva: análisis y propuesta para la enseñanza de los marcadores discursivos en el aula de ELE en Islandia - Basáñez Escobar, Vanessa G., 1982- (2017)
This work aims to study how are introduced the Discourse Markers (DM) in teaching Spanish as a second language (SSL) in Iceland for levels A1/A2. Even though these components are important in Spanish, very little instructional material exists for teaching DM in SSL at the earlier stages. Research on the discourse markers from a pragmatic and pedagogic perspective is practical for the teaching of Spanish as a second language. Much research has been done on discourse markers in Spanish teaching but it is not commonly used by educators when teaching Spanish. Therefore, there was a need for an investigation whose purpose it is to describe how a practical handbook in SSL in the Icelandic classroom can introduce the DM. It will also be demostrate if these components are being taught in SSL in Icelandic classroom today. Activities for the pupils of SSL according to the Common European Framework of Reference for Language (CEFR) are provided, activities which show that the teaching of the DM as linguistic component is an important and a practical tool which allows the author of instructional materials and teachers in SSL to act and find other suggestions that make it easier to the teachers and students to confront any kind of question that can make the teaching and learning of the DM easier. In this thesis a practical handbook and guidelines for educators is provided explaining the importance and benefits of teaching these components appropriately and with the goal that students can achieve satisfactory competence of communication skills in Spanish.